THE EFFECT OF DOUBLE PACKAGING ON THE QUALITY OF FISH BISQUITS CONTAINING CATFISH OIL (Pangasius hypophthalmus) - Purnomo, Agus; Ilza, Mirna; Sukmiwati, Mery (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was intended to determine the effect of double packaging on the quality offish biscuits containing catfish oil (Pangasius hypophthalmus). The using of research methodwas experimental method and the used design was randomized block design (RBD) that wastwo standard of treatment that were HDPE packaging coated carton and alumunium foilcoated carton whereas the treatments were shelf life of 0, 15, 30, 45, and 60 days. Theingredient of making fish biscuits were 33 ml catfish oil, flour, sugar, salt, yolk, chocolatepowder, and soda. Fish biscuits coated with double packaging were HDPE coated carton andalumunium foil coated carton with appropriate shelf life treatments. Fish biscuits wereevaluated for organoleptic, TPC, moisture, fat, and peroxide. The result showed that the typeof double packaging gave the significant effect on appearance, flavor, texture, moisture, fat,peroxide; and the not significant effect on odor and TPC. Alumunium foil coated carton thatwas the superior packaging which can save the quality of fish biscuits until shelf life of 60days with 1,74% moisture, 10,7% fat, 2,70mgEq/kg peroxide, and 5,39sel/g TPC.Keywords: fish biscuits, catfish, shelf life, the type of packaging